HEALTHY HABITS FOR A VIBRANT LIFE: A COMPREHENSIVE GUIDE TO OPTIMAL WELLNESS - Dr. Adil Rashid Malik (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
Abstract Maintaining healthy habits is crucial for achieving optimal wellness and leading a vibrant life. In this research paper, we discuss the importance of healthy habits and their benefits for physical, mental, and emotional well-being. We also provide a comprehensive guide to achieving optimal wellness through healthy habits, including regular exercise, healthy eating, stress management techniques, and other lifestyle choices. By adopting these healthy habits, individuals can reduce the risk of chronic diseases, improve mental health, and enhance their overall well-being. The paper highlights the benefits of regular physical activity, including improved physical health, reduced stress and anxiety, and a lower risk of chronic diseases. It emphasizes the importance of a balanced diet that includes whole grains, fruits, vegetables, and lean proteins to provide essential nutrients and promote overall health